2012
DOI: 10.1007/s11164-012-0670-2
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis, characterization, and biological evaluation of new oxime-phosphazenes

Abstract: Hexachlorocylotriphosphazene (1) was reacted with 4-hydroxy-3-methoxybenzaldehyde to give hexakis[(4-formyl-2-methoxy)phenoxy]cyclotriphosphazene (2). Hexakis[(4-(hydroxyimino)2-methoxy)phenoxy]cyclotriphosphazene (3) was synthesized by reaction of 2 with hydroxlamine hydrochloride in pyridine. Compound 3 was reacted with benzyl chloride, acetyl chloride, allyl bromide, benzoyl chloride, propanoyl chloride, 4-methoxybenzoyl chloride, 2-chlorobenzoyl chloride, chloroacetyl chloride, methyl iodide, and thiophene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The chalcone-phosphazene compounds were generally obtained in high yields. These compounds were characterized by elemental analysis, FT-IR, 1 H, 13 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The chalcone-phosphazene compounds were generally obtained in high yields. These compounds were characterized by elemental analysis, FT-IR, 1 H, 13 …”
Section: Resultsmentioning
confidence: 99%
“…Microanalysis was carried out by a LECO 932 CHNS-O apparatus. 1D ( 1 H, 13 C, 13 C APT and 31 P NMR) spectra were recorded using a Bruker DPX-400 spectrometer. The 1 H, 13 C and 31 P NMR chemical shifts were measured using TMS as an internal standard, whereas those for 31 P were measured using 85% H 3 PO 4 as an external standard.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group observed that the phosphazenes bearing vanillinato and pendant ferrocenyl groups were active against E. coli, S. aureus, B. cereus and B. subtilis, indicating that the antimicrobial activity of the ferrocenyl cyclotriphosphazenes vary depending on the substituents (pyrrolidino, morpholino and vanillinato groups) bonded to the P-atoms [14]. Besides, some phenoxy phosphazenes containing oxime and/or Schiff base groups were effective against E. coli and S. aureus [49,50].…”
Section: Cell Viability Assaymentioning
confidence: 99%